Penyuluhan dan pelatihan pembuatan ekoenzim upaya pemanfaatan limbah organik rumah tangga di desa Tebedak 2 kecamatan Payaraman kabupaten Ogan ilir Sumatera Selatan - Hermansyah, Hermansyah; Hasanudin; Yuliasari, Nova; Rasyid, Riana Sari Puspita; Susilawati (Fakultas Kedokteran Universitas Sriwijaya, 2024)
Ecoenzymes are the result of fermentation of organic materials originating from kitchen waste in the form of fruit or vegetable peels which have many benefits for nature and humans, including as natural plant fertilizer, natural herbicides and pesticides, even in the field of human health. Utilizing fruit and vegetable waste is one of the 'zero waste' movements that can reduce the greenhouse effect. Community Service Program (PPM) activities by utilizing household waste into ecoenzymes were carried out in Tebedak 2 village, Payaraman, Ogan Ilir Regency. This activity is very simple and includes collecting and processing fruit or vegetable waste, mixing it with molasses and water in a ratio of 3: 1: 10, then fermenting or leaving it in a plastic container for 30 to 90 days until ecoenzymes are produced. The training participants were mostly attended by women, with the age range of participants being 20–50 years. The training material delivered, responses to the material delivered, how to implement the material, clarity of the counseling and training material, counseling on whether the information and knowledge provided will be applied, and satisfaction in delivering the counseling and training information were assessed by the majority as very good by the participants. The results of this questionnaire show that this activity is very beneficial for society.